(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
For 35 years, there has been a rapid spread and evolution of laparoscopic surgery in the developed world, where this modality is now regarded as a safe and first choice for up to 98% of all surgical interventions by adequately trained surgeons. The advantages of laparoscopic surgery are now well established. Surgeons must be encouraged to undergo the required training to provide safe laparoscopic surgery. Having pursued my Master’s in Obstetrics and Gynecology at the University of Nairobi, I was posted to Kilifi District Hospital where I served for nine years. I later moved back to Mombasa and ventured into private practice. I developed an interest in and pioneered minimal access surgery in 1994. I developed an immense interest and passion in minimal access surgery and initially pursued a Diploma in Laparoscopic Surgery at the Coimbatore Institute of Gastrointestinal Endosurgery (CIGES). Subsequently, I attended dedicated workshops and additional training in Kiel, Hamburg (Germany), Clermont-Ferrand and Strasbourg (France), and various institutions in Asia and Europe, attending over 40 dedicated workshops, including advanced laparoscopic and hysteroscopic procedures. In 2000, I moved my practice to Nairobi and worked at various private institutions. To increase the awareness of laparoscopic surgery in Kenya. I organized workshops and encouraged many gynecologists and general surgeons to embrace change. I was later fortunate to be invited to several African countries where I trained and mentored numerous surgeons. In conclusion, laparoscopic surgery faces many challenges but is a safe and effective alternative to the traditional open modalities of surgery. The training of surgeons and support staff should be made a priority. I pray that my journey will be an inspiration and encouragement to many in our fraternity in the years ahead.